Sistem Informasi Peminjaman Dan Pembayaran Kredit Usaha (SIPAPEDA) Menggunakan Model Extreme Programming (Study Kasus : DAPM Jembar Kabisa Babakancikao Purwakarta) - Eka Chandra Ramdhani; Ratnawati Ratnawati; Cahyarani Daulika Nugraha (Jurnal Informatika: Jurnal Pengembangan IT, 2019)
The progress of Information and Computer Technology (ICT) has been widely applied. Not even a few business lines use computer sophistication. The use of this technology does not only occur abroad especially in large countries but also in Indonesia. A business credit lending agency is an agency or institution that records business transactions so that the technology of accelerator speed and accuracy is needed. To conduct a problem analysis in this study, a method of question and answer (interview) is carried out and direct assessment of the system that is running, the information system needed is built with extreme programming. This loan and payment application is in the form of an intranet website that can be accessed with a local server and implemented using web programming and MySQL used as database management system software. The making of the loan application and payment of credit is expected to help the problem of data accumulation and the slow pace of information retrieval on the Jembar DAPM, Kabisa, Babakancikao District, Purwakarta, which is still not fully computerized.